PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SCRIPT DALAM UPAYA MENINGKATKAN AKTIVITAS GURU DAN SISWA SERTA HASIL BELAJAR PPKN SISWA SD NEGERI LIWUNG KECAMATAN JANAPRIA - ROHANI ROHANI; FATIMAH FATIMAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This study aims to improve Civics learning outcomes for fourth grade students of SD Negeri Liwung by applying the script type cooperative learning model. This research is a classroom action research conducted at Liwung State Elementary School, the subject of this research is the fourth grade students with a total of 40 students. The results showed that the results of observations of teacher activities in cycle I, the first meeting was in the poor category with a percentage of 62.5%. At the second meeting, the percentage increased to enough category by 70.8%. In the second cycle of the first meeting the category was very good with a percentage of 95.8%, and at the second meeting the category was also very good with a percentage of 100%. The results of the observation of student activities in the first cycle, the first meeting was in the poor category with a percentage of 54.2%, at the second meeting the good category with a percentage of 79.2%. In the second cycle, the first meeting was in the very good category with a percentage of 95.8%, and the second meeting in the very good category with a percentage of 100%. Student learning outcomes in the first cycle obtained classical completeness of 33% in the less category and increased in the second cycle to 72.50% in the good category. From the results of the study, it can be concluded that the application of the script type cooperative learning model can improve Civics learning outcomes for fourth grade students of SD Negeri Liwung. ABSTRAKPenelitian ini bertujuan untuk meningkatkan hasil belajar PKn siswa kelas IV SD Negeri Liwung dengan penerapan model pembelajaran kooperatif tipe Script. Penelitian ini merupakan penelitian tindakan kelas yang dilaksanakan di SD Negeri Liwung, subjek penelitian ini adalah siswa kelas IV dengan jumlah 40 siswa. Hasil penelitian memperlihatkan bahwa Hasil pengamatan aktivitas guru siklus I, pertemuan pertama kategori kurang baik dengan persentase 62,5%. Pada pertemuan kedua meningkat dengan kategori cukup persentase 70,8%. Pada siklus II pertemuan pertama kategori amat baik dengan persentase 95,8%, dan pada pertemuan kedua kategori juga amat baik dengan persentase 100%. Hasil pengamatan aktivitas siswa siklus I, pertemuan pertama kategori kurang baik dengan persentase 54,2 %, pada pertemuan kedua kategori baik dengan persentase 79,2%. Pada siklus II pertemuan pertama kategori amat baik dengan persentase 95,8%, dan pertemuan kedua kategori amat baik dengan persentase 100%. Hasil belajar siswa pada siklus I memperoleh ketuntasan klasikal sebesar 33% dengan kategori kurang dan meningkat pada siklus II menjadi 72,50 % dengan kategori baik. Dari hasil penelitian dapat disimpulkan bahwa penerapan model pembelajaran kooperatif tipe Script dapat meningkatkan hasil belajar PKn siswa kelas IV SD Negeri Liwung.